2010
DOI: 10.1111/j.1755-618x.2010.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Obama, Palin, and Weber: Charisma and Social Change in the 2008 U.S. Election

Abstract: Barack Obama et Sarah Palin sont tous les deux souvent étiquetés en tant que charismatique par le public. Pour évaluer si oui ou non, Obama et Palin démontrent une forme de charisme tel que définit par Weber, leurs rhétoriques et leurs actions sont examinées dans le contexte d'élections passées et dans celui où règne une stagnation politique mise en scène par la guerre des cultures. Là où la connexion entre Palin et le public émerge de son rôle de défenderesse dans la guerre des cultures, Obama a articulée une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Forty-one percent of those who voted in the election were between 18-44 years of age (U.S. Census Bureau, 2008c). Bowden (2010) suggests that Obama articulated a vision of shared community and drew a number of young voters who had previously been disenchanted by the electoral process. Because studies have shown that polls are more accurate the closer they are to the actual election (Crespi, 1988) the time frame in our study design allowed for more accurate recall of the vote and important issues contributing to leader selection.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 97%
“…Forty-one percent of those who voted in the election were between 18-44 years of age (U.S. Census Bureau, 2008c). Bowden (2010) suggests that Obama articulated a vision of shared community and drew a number of young voters who had previously been disenchanted by the electoral process. Because studies have shown that polls are more accurate the closer they are to the actual election (Crespi, 1988) the time frame in our study design allowed for more accurate recall of the vote and important issues contributing to leader selection.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 97%
“…The charismatic leadership in this context translates the relationship between the leader, the followers, and the social circumstances that enable the leader to provide solutions for the problems facing the community. (Bowden, G. 2010) Moreover, the candidate's image composition seems to be influenced by dichotomy between candidate issue positions and candidate persona impressions. (Hacker, K. et al, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%